Prevention of dry socket in mandibular 3rd molars by means of single preoperative oral dose of metronidazole and amoxicillin compared to conventional therapy - Tahseen shabbir Khooharo; Sayed Umer Hassan; Abdul Hafeez Shaikh (Journal of the Pakistan Medical Association, 2021)
Abstract Objective: To compare the efficacy of metronidazole and amoxicillin as preoperative single dose treatment with conventional therapy in prevention of dry socket. Methods: A double blind randomized control trial; patients attending the oral and maxillofacial surgery OPD at DUHS Karachi requiring surgical extraction of madibular 3rd molar during October 2018 till April 2019 were randomly divided into 3 groups. Ethical approval was taken from Institutional Review Board of DUHS Karachi. Consent from patients was also taken. First group was given single preoperative oral dose of 400mg metronidazole one hour before extraction, second group was treated with single oral dose of 500mg amoxicillin an hour before tooth extraction, and both of the groups were given painkillers postoperatively. Third group was given 500mg of Amoxicillin BD, 400mg of metronidazole and painkillers postoperatively. Every group had a follow-up on fifth postoperative day. Results: Dry socket was reported among 19 patients (8.4 %) amongst them 4 were males and 15 were females. Chi-square test was used to calculate the p-value (0.066). Results of the present trial were statistically insignificant. Incidence of dry socket in amoxicillin group was 3 (5.5%), in metronidazole was 4 (7.5) and in conventional therapy group was 12(16%). Conclusion: Present trial was not effective in preventing the occurrence of dry socket by means of single preoperative oral dose of metronidazole and amoxicillin compared to conventional therapy. However, clinically percentage of occurrence of dry socket was higher in conventional group compared to amoxicillin and metronidazole group. Clinical Trial Number: NCT03992144. Continuous...